Analisis Language Toxic dalam Aplikasi Game Online Mobile Legends - Endang Sholihatin; Ahmad Thariq Maulana; Muhammad Antariksa Dharu; Handika Faiz Rahmawan; Rizky Farrel Ardian Purwanto; Shendy Achmad Himawan (STIE Amkop Makassar, 2024)
Mobile Legends is a popular online game Android-based that can played on mobile devices such as smartphones. This research aims to determine the form of toxic language from Mobile Legends online game players, knowing the factors that cause Mobile Legends online game players to express toxic language and find out whether the online game Mobile Legends can influence a person's language behavior. Using qualitative and quantitative research methods, data collection was carried out by distributing questionnaires and indirect interviews. The research result showed that 1) forms of toxic language from Mobile Legends players include five categories, namely a person's weakness, relatives/family members, names of animals, committing obscenities, and committing vile; 2) factors that cause Mobile Legends players to express toxic language uncooperative teams, repeated defeats, signal problems, the emergence of differences in how to play, and there is a condition of mutual teasing; and 3) the online game Mobile Legends can influence a person's language behavior because a person becomes more likely to speak toxic language, it affects daily behavior, it makes a person more rude, it affects the mental state, changes a person's personality, normalizes harsh sentences, can eliminate politeness, and can influence language behavior towards older people.